Implementasi Model Prototye Dalam Pembuatan Aplikasi Pemesanan dan Perawatan Taxi Berbasis Website - yoki firmansyah; Reza Maulana; Safitri Linawati; Rizaldi Rabbani (FKOM UNIKU, 2024)
Travel Janyakng Group is a travel company that operates in the car rental sector, where currently the company is facing several problems such as consumer inconvenience in ordering, apart from that, there are also difficulties in managing car maintenance data at the company. Seeing these problems, with the era of information technology Currently, companies can take steps, namely creating a website-based information system with the aim of improving the taxi ordering and maintenance process, as well as improving service to consumers. There are several methods used, namely the software development method using a prototype model and the data collection method using observation, interviews and literature study, while for building website-based applications the PHP and MySQL languages ​​are used, while for the application prototype the Balsamiq Wireframes application is used. In this application there will be three activities involved, namely user, admin and taxi driver. By using this application, it is hoped that the company can improve the quality of service to customers, make the ordering and maintenance process more efficient and the company can make better strategic decisions